Contributing to an integrated profession: a model-based examination of the A-ONE. (4th March 2017) - Árnadóttir, Guðrún
Abstract: Yerxa's [1] model of an integrated profession depicts a circular scholarly process whereby ideas formed in practice are subjected to research and then returned to practice through education. This knowledge-generating cycle supports occupational science and the development of our professional identity. The aim of this article is to demonstrate how Yerxa's model was used to evaluate if three developmental cycles of the ADL-Focused Occupation-Based Neurobehavioral Evaluation (A-ONE) sufficiently represented all necessary model components required for implementation into practice. The three cycles were historical, educational and measurement. The necessary components included: (a) dilemmas in practice, (b) new ideas that emerged from those practice issues, (c) research to test those ideas and (d) education designed to integrate new knowledge into practice. The results of this analysis of the A-ONE supported adequate research related to ideas from practice being implemented back into practice. Through using the model of an integrated profession to reflect on ideas ignited within practice, and then implementing research to explore the potential contribution of those ideas to knowledge generation, we gain the power to influence the future development of occupational science and the profession.